(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Shale Oil (SO) has emerged as an attractive additional supply of conventional crude oil throughout the world in recent years. Shale oil quality evaluation includes a variety of geochemical parameters. In this research, we propose a novel Integrated shale oil evaluation approach. This method firstly determines the relative weights of parameters using rough set theory. Finally, Multiple Criteria Ranking by Alternative Trace (MCRAT) technique is utilized to calculate the rank of Shale oil wells. Twenty-seven samples of shale oil were collected from various distinct well sites. Twelve different geochemical parameters were examined in the gathered samples in order to determine the grade of the shale oil. The results reveal that shale oil sample 17 geochemical parameters, with shale oil grade I is the best collection parameters concentrations. The suggested approach is compared to five Multi-Criteria Decision Making (MCDM) approaches to demonstrate its effectiveness. The obtained results gained by the MCRAT Integrated with Rough Set Theory (RST) is clear in ideas and easy in computation, which may be effectively applied to address a variety of problems, both similar and different.